Importance of Dynamic Inflow in Model Predictive Control of Wind Turbines. Issue 30 (2015) - Odgaaard, Peter Fogh; Knudsen, Torben; Overgaard, Anders; Steffensen, Henrik; Jørgensen, Marten
Abstract: The efficiency of including dynamic inflow in the model based design of wind turbine controller has been discussed for many years in the wind energy community with out getting to a safe conclusion. This paper delivers a good argument in favor of including dynamic inflow. The main contributions are the use of a very simple inflow model, developed by one of the authors and the use of Pareto fronts to facilitate a safe conclusion. The approach is to compare MPC controllers designed with respectively without including dynamic inflow for a mean wind speed just above rated where this dynamics are most pronounces. For this the well accepted NREL 5MW reference turbine simulated with FAST is used. The main result is a reduction in tower fatigue load at 22% while power error, rotor speed error, generator torque and pitch rate is improved from 2 to 33%.